1965
DOI: 10.1017/s0003356100022261
|View full text |Cite
|
Sign up to set email alerts
|

The feed intake of milk cows II. The effect of roughage quality during late pregnancy and lactation

Abstract: SUMMARY1. An experiment is described in which the individual feed intakes of 16 cows under winter housing conditions in yards, during the transition to spring grazing and on. summer grazing, were determined by faecal indexdigestibility methods. The influence of quality of feed before calving on intake and subsequent performance and the influence of pasture quality and availability on feed intake were included in the study.2. The provision of a diet of 67% organic matter digestibility, either as high quality ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1966
1966
1980
1980

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Good relationships are generally found between digestibility of feed and intake of ruminants (Holmes and Jones 1965), but Thomas and Campling (1976) concluded that at high levels of digestibility (over 70%), there may no longer be any relationship.…”
Section: Nutritional Variablesmentioning
confidence: 99%
“…Good relationships are generally found between digestibility of feed and intake of ruminants (Holmes and Jones 1965), but Thomas and Campling (1976) concluded that at high levels of digestibility (over 70%), there may no longer be any relationship.…”
Section: Nutritional Variablesmentioning
confidence: 99%
“…They had been sown in 1960 and 1962 respectively with the same grass seeds mixture of timothy (Phleum pratense), meadow fescue (Festuca pratensis) and white clover (Trifolium repens) and had both been grazed by dairy cows in previous years and used in experiments reported by Holmes and Jones (1965), Holmes, Jones and Adeline (1966) and Holmes and Curran (1967). Two adjacent pastures were used.…”
Section: Treatmentsmentioning
confidence: 99%
“…Residual SD ± 1-10 (2) When Y = digestibility of herbage organic matter (%) and X = nitrogen content of the faecal organic matter (%) For treatment RS, in which the cows received an appreciable proportion of concentrates in their diet, this method was inappropriate and the method of Holmes and Jones (1965) was adopted. This consisted of estimating the faecal output attributable to concentrates by assuming that the digestibility of the concentrate organic matter was 80%, and then applying the same digestion coefficient to the pasture component of the faeces as that adopted for the cattle receiving the corresponding pasture only (i.e.…”
Section: Recordsmentioning
confidence: 99%